The ballroom dance pack - Laird, Walter (London New York Dorling Kindersley Boston Distributed by Houghton Mifflin Co, 1994)
This comprehensive teaching program introduces you to the six most popular social dances: the waltz, the quickstep, the tango, the rumba, the samba, and the cha-cha. The full-color guide shows you all the steps and combinations necessary to dance complete figures around the floor, and contains special practice exercises to loosen you up and help you master the essential rhytms
How to use the pack -- Ballroom dancing-an introduction -- The Waltz -- The Quickstep -- The Tango -- The Cha-cha -- The Samba -- The Rumba
Includes 6 step cards and 2 feet templates inserted in pocket
Keywords: Ballroom dancing